At the crossroads of career and camaraderie - Alias, Mawaddah; Hassan, Arif (IIUM Press, 2012)
This case study presents a sunny scenario of a ard-working, talented and competitive employee who is seen to be recognised and rewarded for her efforts by her superiors. This case analysis elucidates the fact that for achieving success,recognition and excellence in an organisation, two factors are of substantial importance. One would be personal attributes of an employee such as hard-work, competitiveness, talent and skills and second the presence of an inspirational,motivating, helpful, friendly, trusting, supportive, and an unbiased leader. The case study clearly depicts that when these two factors combine, they bring about highly positive developments for the employee as well as for the entire organisation. However, difficult choices are to be made by a manager and the employee herself when opportunities for recognition and promotion knock on the door.